1966
DOI: 10.1107/s0365110x66003839
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the structure of β-tricaprin

Abstract: The B-phase of tricaprin (C3306H62) is triclinic, space group P i, with the following unit-cell dimensions: a--5.488_+0.01 A ct= 85.35 _+ 0.15 ° b = 12" 176 _+ 0.03 # = 87.27 +_ 0.15 c =26"93 _+0.07 y=79-28 + 0.15Three-dimensional data collected at ambient temperature, which is only a few degrees below the melting point of 31"9°C, have been used to refine the structure to a final R= 5.1%. The molecules are packed as a modified 'tuning fork' in which two chains with two glyceryl carbon atoms and two ester oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(77 citation statements)
references
References 4 publications
5
72
0
Order By: Relevance
“…3. Tricaprin (4,20) is an obvious exception in that the chain folds nearly at right angles at the 2 carbon. In PP2, DMPC (15), and 1,2-dilauroyl-rac-glycero-3-phosphoethanolamine (19) (not shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3. Tricaprin (4,20) is an obvious exception in that the chain folds nearly at right angles at the 2 carbon. In PP2, DMPC (15), and 1,2-dilauroyl-rac-glycero-3-phosphoethanolamine (19) (not shown in Fig.…”
mentioning
confidence: 99%
“…The structure of the , form of the single-acid triacylglycerols tricaprin (4,20) and trilaurin (5) are isostructural and form a tuning-fork conformation with the glycerol bent so that two glycerol carbons lie in the bilayer plane and the third projects up from it (Fig. 3).…”
mentioning
confidence: 99%
“…The monoacid (n n n) class of TAGs has been studied in most detail, using single-crystal data (n = 10, Jensen & Mabis, 1966;n = 12, Larsson, 1965;Gibon et al, 1984; n = 16, van Langevelde et al, 1999) as well as high-resolution synchrotron powder diffraction (HR-SPD) data (n = 14, 18; van Langevelde et al, 2001a; n = 13, van Langevelde et al, 2001b;n = 15, 17, 19;Helmholdt et al, 2002) and confirmed earlier postulations of the packing of this type of polymorph (Lutton, 1971(Lutton, , 1972de Jong & van Soest, 1978). The singlecrystal packing of the (n n n) analogue EEE 1 (Culot et al, 2000) is also in accordance with this result.…”
Section: Introductionmentioning
confidence: 99%
“…A closer examination of the isotropic displacement parameters show the majority of them are predominantly unspecific. This is quite interesting since diffraction studies on lipids or other cationic surfactants studied at room temperature consistently show strong anisotropy due to their vibrational motion about their chain axis 38 and excessive thermal motion can gave rise to disorder 39 or partial liquefaction of the structure. 40 Atomic displacement parameters for the chain ends of Bzth-Cl or Bzth-Br C (25); C(26), C(27) and C (22) were analyzed in terms of rigid body motion 40,41 and the physical significance of the obtained parameters were examined by a Hirshfeld rigid body test.…”
Section: A Structure Of the Hydrated Bzth Halide Saltsmentioning
confidence: 99%